Reentrance transition in two lane bidirectional transport system with bottlenecks. (December 2022) - S, Tamizhazhagan; Verma, Atul Kumar
Abstract: Inspired from the vehicular traffic scenarios, including the companionship of two consecutive speed bumps placed within a sufficient distance on the road, we investigate a bidirectional two-lane symmetrically coupled totally asymmetric simple exclusion process with two bottlenecks in the presence of Langmuir kinetics. The steady-state system dynamics in terms of density profiles, phase diagrams, phase transitions, and shock dynamics are investigated thoroughly, exploiting hybrid mean-field theory with various strengths of the bottleneck and lane changing rates which match well with Monte Carlo simulation outcomes. It has been detected that the qualitative and quantitative topology of phase diagrams crucially depend on bottleneck and lane switching rate, emanating in monotonic as well as non-monotonic alterations in the number of steady-state phases. We observe that the effect of the bottlenecks is weakened for the increasing values of the lane changing rate. The proposed study provides many novel mixed phases resulting in bulk-induced phase transitions. The interplay between bottlenecks, lane switching, bidirectional movement, and Langmuir kinetics produces unique phenomena, including reentrance transition and phase division of mixed shock region for comparatively lower lane switching rate. Highlights: The dynamics of the symmetrically coupled TASEP system with two bottlenecks are investigated. Mean-field approximation is utilized to explore the stationary system properties. Phase diagrams display a rich behavior, with many distinct phases, including several new mixed phases. Emergence of mixed phases leads to bulk-induced phase transitions. The interplay between bottlenecks and lane switching leads to novel features, including Reentrance transition and phase division.